The Efficiency of Hand Tricks in Learning Trigonometric Ratios - Delima, Christian M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study investigated how hand tricks influenced the students' achievement in trigonometric ratios. Using a quasi-experimental design and purposive sampling, twenty students were the survey respondents: ten of whom took as a control group, and ten took as an experimental group. Through limited face-to-face classes, the researcher selected respondents from Grade 9 students at Bonifacio National High School. The research instruments used in this study are two sets of lesson plans, a pretest, and a post-test. The study revealed that the traditional method and hand tricks effectively teach trigonometric ratios. However, results also found that it was more effective to teach trigonometric ratios when using the hand tricks. The study concluded that the traditional and hand tricks were considered effective in teaching trigonometric ratios. Though, those students who participated in the use of hand tricks in teaching performed better in solving trigonometric ratios than those students who trained using the conventional method. The use of hand tricks helps students with difficulty in memorizing trigonometric ratios. The researcher recommended that we always use hand tricks in teaching trigonometric ratios. It is also recommended for complete and thorough teaching of mathematics topics throughout the year to reinforce mathematics teaching and learning. Moreover, hand tricks are used in learning trigonometric ratios and preparing for advanced trigonometric lessons.